Risk-Based Tax Audits : Approaches and Country Experiences - Khwaja, Munawer Sultan (World Bank, 2012)
Revenue administration is a major interface between the state and its citizens. A good revenue administration is, therefore, an important attribute of good government. As a result, in recent years, policy makers have become increasingly aware of the importance of policies that will promote business development while ensuring voluntary tax compliance. In the modern context, it is neither desirable nor feasible to examine or inspect every single taxpayer. The revenue administration, therefore, has to rely on effective management of compliance. Promoting voluntary compliance, achieved through a self-assessment system in which taxpayers comply with their tax obligations without intervention from tax officials, requires developing modern approaches to audits based on risk management. The impact of audits critically depends on a properly designed audit selection strategy focused on high-risk taxpayers to provide the most cost-effective outcome. This, in itself, contributes to promoting voluntary compliance. Risk-based country audits: approaches and country experiences are an important study of this critical revenue function of compliance management.